Siltito glauconítico calcinado e não calcinado como fertilizantes para Urochloa brizantha cv. Marandú - Violatti, Isabel Cristina Acciardi (2018)
Brazil imports most part of the potassic fertilizers consumed in agriculture, mainly due to Brazilian soils having low amounts of macronutrients and lack of self-sufficiency in the supply of raw materials for the production of fertilizers. Therefore, the search for alternative sources to meet the need for internal consumption of fertilizers became fundamental. The objective of this study was to evaluate the agronomic efficiency and residual effect of glauconitic siltite non-calcined and calcined microgranulated and fine granulated in the culture of Urochloa brizantha cv. Marandú (Syn. Brachiaria brizantha), as a source of potassium (K), silicon (Si), manganese (Mn), calcium (Ca) and magnesium (Mg). Two experiments were performed, cultivating brachiaria in a Typic Dystrustox (clayey soil) and in a Typic Quartzipsamment (sandy soil). The treatments were constituted by K2O doses from the galuconitic siltite (5, 20, 40 and 80 mg dm-3 of K2O), with an additional control treatment (0 mg dm-3 of K2O) and three additional positive treatments for comparison (KCl in the dose 80 mg dm-3 of K2O, KCl + Wollastonite at the dose 80 mg dm-3 of K2O + 270 mg dm-3 of Si and KCl + MnSO4 at a dose 80 mg dm-3 of K2O + 2 mg dm-3 of Mn) and were also composed of K2O doses from the glauconitic siltite microgranulated and fine granulated (80, 160, 240 and 320 mg dm-3 of K2O), besides an additional control treatment (0 mg dm-3 of K2O) and two additional positive treatments (KCl in the dose 80 mg dm-3 of K2O and KCl + Wollastonite at the dose 80 mg dm-3 of K2O + 390 mg dm-3 of Si). The experiments were conducted with four replicates in a completely randomized design and plots consisting of plastic vessels with 5 kg of air dried fine soil (ADFS). Three successive crop cuts were performed, as well as soil samples collected after the third cut in order to evaluate the residual effect of the source. It was possible to verify that the glauconitic siltite increased DMAP, with DMAP results higher than KCl in the at higher dose of the third cut. For the calcined glauconitic siltite, the same behavior was observed, however, presenting higher results than KCl in the three higher doses used. In addition, the AEI (%) of the tested sources was higher than the standard after the last cut of the forage plants, demonstrating the residual and potential effect of the products in the substitution of soluble sources. The sources tested were efficient in providing K, Si and Mn to the plants. For the majority of treatments, the tested products responded similarly to the treatments in which KCl, KCl + Wollastonite and KCl + MnSO4 were applied in the first cultures, presenting higher values in the third crop, which shows the residual and potential effect of the rocks in providing nutrients in successive crops.